A severe contact burn from an exhaust pipe at the lower extremity: Primary macrovascular reconstruction was found to be effective - Yoshitaka Matsuura (Elsevier, 2022)
Contact burn is a challenging injury to manage, often penetrating very deep through the skin and into the muscle. The temperature and duration of contact with hot objects determine the burn depth. A 42-year-old man driving a motorbike fell down during a traffic collision. He unfortunately slid under a car in a prone position, and his left foot, leg and posterior thigh were injured by a deep contact burn from the hot exhaust pipe. The damage progressed to the muscle, tendon and bone. An anterolateral thigh free flap procedure was performed for primary reconstruction to cover the Achilles tendon, bone and heel. Flap congestion occurred after the operation, but we managed to avoid flap necrosis by adding vein transfer. Successful microvascular reconstruction contributed to his regaining the ability to walk. He was able to walk on his own when discharged from the hospital despite a severe contact burn.